Transferência de Embriões em Tempo Fixo em Bovinos. - Domingues, Éverton Rosa (Universidade Federal do Tocantins, 2023)
This report describes the activities developed during the required supervised curricular internship at Embriotec Animal Reproduction Company, held in the period from August 2, 2017 to October 15, 2017, totaling 360 hours, under the guidance of Professor Francisca Elda Ferreira Dias and supervision of MV Dr. Alexandre Sardinha Cavalhêdo. During the internship period, several activities related to bovine reproduction were developed, among them, andrological examinations in bulls, ultrasound examinations of pregnancy diagnosis, embryo transfer protocols at fixed time, among other activities. All activities were developed in rural properties located in the state of Goiás and in the company's properties. This report provides a more detailed description of the biotechnology embryo transfer at fixed time (TETF).